IFE EFE Analysis of A Social Enterprise Business Strategy - Puspita, Evi Anggraini; Nurfitriya, Mira; Koeswandi, Tika Annisa Lestari (Universitas Pendidikan Indonesia, 2024)
The problem with Kawoel’s MSMEs is the dominance of decreased income, therefore MSMEs need the right business strategy and are suitable for this social enterprise. The object of this research was carried out at a social enterprise company, namely Kawoel's MSMEs. Therefore, the objectives of this study are: 1) to find out an overview of the business strategy carried out by MSMEs at Kawoel's, 2) to find out the strengths, weaknesses, opportunities and threats of Kawoel's MSMEs, 3) to find out alternative business strategy formulations using SWOT Internal Factor Evaluation (IFE) matrix analysis and External Factor Evaluation (EFE) matrix for MSMEs in Kawoel's. This type of research was descriptive qualitative with data collection techniques using observation, interviews, and literature study. This study uses a single variable, namely business strategy, to analyse business strategy in Kawoel's MSMEs using the IFE and EFE matrix tools. The business strategy implemented by Kawoel's had not been maximised so that it had a negative impact on its business. The results of the IFE and IFE matrix for Kawoel's business strategy formulation are in quadrant V, which means that it can be done with a maintain and maintain strategy.